Stephania tetrandra S. Moore: a promising candidate drug for treating diabetic kidney disease - Wang, Wenru; Li, Jixin; Yan, Yan; Zeng, Qin; Yan, Lei; Wang, Xinhui; Liang, Ying; Yu, Renhuan (Frontiers in Pharmacology, 2025)
Diabetic kidney disease (DKD) is a common microvascular complication of diabetes. With the continuous rise in the prevalence of diabetes, it has become the primary cause of end-stage renal disease. Currently, there are no effective clinical treatments available to reverse the progression of DKD. Stephania tetrandra S. Moore, a traditional Chinese medicine, has demonstrated significant value in the prevention and treatment of DKD due to its active components. This study focuses on exploring the molecular mechanisms through which the primary active components of S. tetrandra, tetrandrine/sinomenine and fangchinoline, exert renal protective effects via multiple pathways, including regulating inflammatory responses, antagonizing oxidative stress, improving glomerular endothelial function, modulating podocyte damage, and intervening in lipid metabolism disorders. These findings provide a theoretical basis for the development of novel therapeutic agents for DKD.